2009
DOI: 10.1055/s-0029-1240623
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechins: Inhibitors of Glycerol-3-Phosphate Dehydrogenase

Abstract: Green tea catechins, especially (-)-epigallocatechin-3-gallate (EGCG), are known to regulate obesity and fat accumulation. We performed a kinetic analysis in a cell-free system to determine the mode of inhibition of glycerol-3-phosphate dehydrogenase (GPDH; EC 1.1.1.8) by EGCG. GPDH catalyzes the beta-nicotinamide adenine dinucleotide (NADH)-dependent reduction of dihydroxyacetone phosphate (DHAP) to yield glycerol-3-phosphate, which serves as one of the major precursors of triacylglycerols. We found that EGCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…In this study, we found that when Panc‐1 cells were treated with oxamate, a specific LDH inhibitor (Novoa et al , ), the cytosolic NADH level was significantly increased (by 39%, P < 0.001, Fig A), supporting the concept that LDHA is important for the anaerobic conversion of NADH to NAD + in the cytosol. Moreover, in Panc‐1 cells, inhibition of the malate–aspartate shuttle and the glycerol phosphate shuttle by AOA [a specific malate–aspartate shuttle inhibitor (Eto et al , )] and epigallocatechin‐3‐gallate [EGCG, a multi‐functional agent which can inhibit GPDH (Kao et al , )], respectively, led to a significant increases in the cytosolic NADH level (by 25%, P < 0.001 for AOA treatment and by 15%, P < 0.01 for EGCG treatment) (Fig A). These findings indicate that the malate–aspartate shuttle contributes more than the glycerol phosphate shuttle to regulate cytosolic NADH redox homeostasis in Panc‐1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that when Panc‐1 cells were treated with oxamate, a specific LDH inhibitor (Novoa et al , ), the cytosolic NADH level was significantly increased (by 39%, P < 0.001, Fig A), supporting the concept that LDHA is important for the anaerobic conversion of NADH to NAD + in the cytosol. Moreover, in Panc‐1 cells, inhibition of the malate–aspartate shuttle and the glycerol phosphate shuttle by AOA [a specific malate–aspartate shuttle inhibitor (Eto et al , )] and epigallocatechin‐3‐gallate [EGCG, a multi‐functional agent which can inhibit GPDH (Kao et al , )], respectively, led to a significant increases in the cytosolic NADH level (by 25%, P < 0.001 for AOA treatment and by 15%, P < 0.01 for EGCG treatment) (Fig A). These findings indicate that the malate–aspartate shuttle contributes more than the glycerol phosphate shuttle to regulate cytosolic NADH redox homeostasis in Panc‐1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Other in vivo findings indicated that EGCG reduced food uptake and lipid absorption and stimulated fat oxidation and fecal lipid excretion [see details in reviews by Kao et al, 2006; Lin and Lin‐Shiau, 2006; Wolfram et al, 2006; ]. These findings were supported by in vitro data showing that EGCG is responsible for the following: (1) increasing the rate of oxygen consumption in brown adipose tissue, synergistically with caffeine and norepinephrine []; (2) regulating the activities and expression of various enzymes related to lipid anabolism and catabolism [], including acetyl‐CoA carboxylase [], fatty acid synthase [], glycerol‐3‐phosphate dehydrogenase [], pancreatic lipase [], lipoxygenase [], hormone‐sensitive lipase [], and adenosine monophosphate (AMP)‐activated protein kinase (AMPK) []; (3) inhibiting the adipogenic differentiation of preadipocytes into adipocytes []; (4) regulating adipokine secretion [] and glucose uptake [] of adipocytes; and (5) reducing serum‐ and insulin‐induced increases in cell numbers []. The antiobesity effects of EGCG may be also explained by its ability to induce functional changes in other target tissues (e.g., the digestive organs, liver, pancreas, brain, heart) and proteins (e.g., catechol‐ O ‐methyltransferase, caspase‐3, cyclin‐dependent kinases, fatty acid transporter, p53, sodium‐dependent glucose transporters, uncoupling proteins, vimentin) [].…”
Section: Introductionmentioning
confidence: 91%
“…EGCG suppressed FAS induction by epidermal growth factor (EGF) by inhibiting the phosphatidylinositol 3-kinase (PI3K)/Akt – mediated signaling. Kao et al [43] found that EGCG inhibited glycerol-3-phosphate dehydrogenase (GPDH) with IC 50 value of 20 μM in a cell-free system. Also they revealed that EGCG was a noncompetitor of GPDH substrates, NADH and dihydroxyacetone phosphate (DHAP) with respective inhibition constants (K i ) of 18 and 31 μM.…”
Section: Prevention Of Obesity By Green Tea Polyphenolsmentioning
confidence: 99%